Safety, tolerability, and bioavailability of topical SAR 1118, a novel antagonist of lymphocyte function-associated antigen-1: a phase 1b study - Paskowitz, D M; Nguyen, Q D; Gehlbach, P; Handa, J T; Solomon, S; Stark, W; Shaikh, O; Semba, C; Gadek, T R; Do, D V (Eye (London), 2012)
Purpose A growing body of evidence points to a role for inflammation mediated by lymphocyte function-associated antigen-1 (LFA-1) and its ligand intercellular adhesion molecule-1 in the pathogenesis of diabetic macular oedema. This phase 1b clinical trial assessed the safety, tolerability, and pharmacokinetics of topically administered SAR 1118, a novel LFA-1 antagonist, in human subjects. Methods In this prospective, randomized, double-masked trial, 13 subjects scheduled for vitrectomy received one of three concentrations of topical SAR 1118 (0.1, 1.0, or 5.0%) twice daily for 1 week before surgery. Undiluted aqueous and vitreous samples were collected at surgery and analysed for the concentration of the medication. Results All subjects completed the entire course of medication. The only adverse events reported were instillation site irritation (4/13, 31%) and dysgeusia (3/13, 23%). These were mild and transient, occurring at the highest dose. Mean concentrations (ng/ml) of SAR 1118 in the aqueous humour were 0.25, 37.2, and 101.1 for the 0.1%, 1.0%, and 5.0% dose groups, respectively. SAR 1118 was below the level of detection (0.5 ng/ml) for all vitreous samples except in a single subject who had a history of prior vitrectomy and a dislocated intraocular lens. Conclusions Topical SAR 1118 was safe and well tolerated, and dose-dependent levels of drug were detected in aqueous. However, vitreous levels were below the threshold of detection with the concentrations tested. Further investigation of this medication for posterior segment applications would require intravitreal delivery or chemical modification of the drug.